2003
DOI: 10.1074/jbc.m308300200
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of a Chemical Nuclease to Investigate the Location and Orientation of the Escherichia coli RNA Polymerase α Subunit C-terminal Domains at Simple Promoters That Are Activated by Cyclic AMP Receptor Protein

Abstract: The C-terminal domain of the ␣ subunit (␣CTD) of bacterial RNA polymerase plays an important role in promoter recognition. It is known that ␣CTD binds to the DNA minor groove at different locations at different promoters via a surface-exposed determinant, the 265 determinant. Here we describe experiments that permit us to determine the location and orientation of binding of ␣CTD at any promoter. In these experiments, a DNA cleavage reagent is attached to specific locations on opposite faces of the RNA polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 37 publications
4
32
0
Order By: Relevance
“…This result agrees with recent work (2) using an artificial chemical nuclease, which demonstrated that a single subunit of ␣CTD binds immediately upstream of FNR at a class II promoter in a position and orientation that would place ␣CTD region 285-288 in close proximity to FNR-AR1 region 184-192. Taken together, these data suggest that the region of ␣CTD required for activation by FNR and CRP overlap since CRP also requires region 285-288 of ␣CTD to activate transcription (27,28) and that ␣CTD binds in a similar orientation relative to both FNR and CRP at a class II promoter (18).…”
Section: Discussionmentioning
confidence: 78%
“…This result agrees with recent work (2) using an artificial chemical nuclease, which demonstrated that a single subunit of ␣CTD binds immediately upstream of FNR at a class II promoter in a position and orientation that would place ␣CTD region 285-288 in close proximity to FNR-AR1 region 184-192. Taken together, these data suggest that the region of ␣CTD required for activation by FNR and CRP overlap since CRP also requires region 285-288 of ␣CTD to activate transcription (27,28) and that ␣CTD binds in a similar orientation relative to both FNR and CRP at a class II promoter (18).…”
Section: Discussionmentioning
confidence: 78%
“…[29][30][31] Although UP elements are usually located between −40 and − 60, DNA bending by CRP or IHF has been shown to allow αCTD to bind UP elements at −80 and − 90. 32,33 P pilA variants in which the A + T runs were replaced or translocated were constructed to test whether these A + T runs are important for promoter activity. As shown in Fig.…”
Section: A + T Runs Upstream Of Crp-s Sites Are Required For Promotermentioning
confidence: 99%
“…At Class I CAP-dependent promoters, one ␣CTD protomer-interchangeably ␣CTD I or ␣CT-D II -interacts with CAP (1,2,(12)(13)(14)(15). The other ␣CTD protomer interacts nonspecifically with upstream DNA (1,2,12,13,16).…”
mentioning
confidence: 99%